Making Rankings Credible: How Ranking Creators Navigate Trials Of Strength - Strietzel, Elisabeth; Tobias, Can David (Serendipities. Journal for the Sociology and History of the Social Sciences, 2026)
In this article, we take a closer look at the production of social knowledge beyond conventional academic sites in two NGOs that produce rankings of nation states. Whereas extant literature on rankings has mainly focused on the critique of methodologies or the inherent power of numbers, we suggest viewing them as webs of practices aimed at generating credible knowledge about the world. Using Latour’s concept of trials of strength and applying it to two in-depth case studies, we investigate these practices empirically to unpack how these organisations attempt to create epistemic credibility.